1998
DOI: 10.1093/ndt/13.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus bacteraemia among patients undergoing dialysis--focus on dialysis catheter-related cases

Abstract: Patients on dialysis are at a high risk of S. aureus bacteraemia and they have a four times higher mortality from central venous catheter-related S. aureus bacteraemia than other patients. There is need for prospective studies in which patients as well as catheters are followed more thoroughly to study the pathogenesis of dialysis catheter-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…In hemodialysis patients with CRB S.aureus is an independent risk factor for both infectious complications and failure of bacteremia treatment (10) .A singlecenter, retrospective study found that, compared with patients not on dialysis, those on dialysis (379 hemodialysis and 31 peritoneal dialysis patients) were four times more likely to die from S. aureus CRB staphylococcus induced (5.3% vs. 1.3%; P<0.001). (11).…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients with CRB S.aureus is an independent risk factor for both infectious complications and failure of bacteremia treatment (10) .A singlecenter, retrospective study found that, compared with patients not on dialysis, those on dialysis (379 hemodialysis and 31 peritoneal dialysis patients) were four times more likely to die from S. aureus CRB staphylococcus induced (5.3% vs. 1.3%; P<0.001). (11).…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients with CRB S.aureus is an independent risk factor for both infectious complications and failure of bacteremia treatment (10) .A singlecenter, retrospective study found that, compared with patients not on dialysis, those on dialysis (379 hemodialysis and 31 peritoneal dialysis patients) were four times more likely to die from S. aureus CRB staphylococcus induced (5.3% vs. 1.3%; P<0.001). (11).…”
Section: Discussionmentioning
confidence: 99%
“…[9,14,16,17] Third, according to microbiology patterns observed in our own institution, 62% of all S. aureus isolated are methicillin-resistant, and these patients require a thrice-weekly dialysis in a hospital facility; thus, the occurrence of MRSA bacteremia may represent a true nosocomial infection carrying a devastating virulence in an immune dysregulated uremic host. [18][19][20] The mortality rate of CNE in the general population ranges from 7-32% [12,13] ; the outcome is even less optimistic in endocarditis patients with true negative blood culture than in patients with previous antibiotics treatment. [21] Furthermore, mortality is increased in patients receiving delayed treatment and in those still febrile after one week of therapy.…”
Section: Discussionmentioning
confidence: 99%